Organic residue, limestone, gypsum, and phosphorus adsorption by lowland soils (Scientia Agricola, 2002)
Organic residue application is a low cost alternative to reduce the use of inorganic fertilizers and correctives. In order to study the effect of organic residues, limestone and gypsum application on phosphorus adsorption by lowland soils, four experiments were carried out. A Mesic Organosol (OY), a Melanic Gleysol (MG), a Haplic Gleysol (GX), and a Fluvic Neosol (RU) were used in a completely randomized design and factorial scheme (3 x 2), with five replicates: three soil amendment practices (limestone, gypsum and no corrective) and two levels of organic residue (with and without corral manure). Soil samples were incubated for 60 days, with and without organic residue incorporation. After this period, we applied the corrective and incubated the soil for 30 days, then P and basic fertilization (macro and micronutrients) were applied and the soil was incubated for additional 60 days. Equilibrium phosphorus, maximum phosphate adsorption capacity, pH, exchangeable Al and phosphorus-buffering index were measured. Organic residue and limestone application increased soil pH and reduced exchangeable Al, decreasing P adsorption. Gypsum application did not increase the pH but reduced exchangeable Al and P adsorption.